Роль университетской библиотеки в подготовке студента к пользованию книгой - Пээп, Лайне; Синкявичюс, Клеменсас (Knygotyra, 1974)
Today, with the enormous development of science and technology, and when the general mass of information doubles every 7–8 years, the knowledge acquired by a university graduate is not expected to retain its practical utility for more than 10–12 years. As a result, a young specialist, not conversant with the methods of independent study essential to replenish his knowledge through the use of books, becomes liable to disqualification in a very short time.The success of a library in providing the readers material required for such replenishment depends, to a certain extent, on the so-called „bibliographical literacy“ of the readers. It was already in the pre-war days that a course on bibliography was read in several institutions of our country. In 1959, this course was included into the curriculum of all higher institutions. As lecturers for the course, the workers of libraries were expected to acquire and possess new professional qualifications.In recent years, the course on library-bibliographical knowledge has been re-organized in several institutions in the U.S.S.R. with the aim of converting it into a full university course, imparting to the students the knowledge requisite for orientation in the present-day flow of information, not only during the period of studies but also after finishing the same. Inclusion of the course on the Basis of Information into the general course is a very complicated and responsible task for the library staff.Universities of several foreign countries have also had some experience in teaching students the principles of bibliography and information. During the last few years a keener interest is being taken into the problem of bibliographical preparation of students by several countries, e.g., Czechoslovakia, U.S.A., GDR, FRG, France, Poland, Great Britain etc. The problem of training the users of information has been discussed in many conferences of FID.A university library has the tendency to become a methodical and pedagogical centre of the university, assisting the student in acquiring the knowledge requisite not only for the successful execution of the academic course but also to maintain the qualification level in the period of practical work. Taking this aspect into consideration, it is desirable to introduce amendments while determining the role of a library in a university, and to offer assistance to the library staff in effecting more rational and operative solution to this problem.